An efficient algorithm for estimating the parameters of superimposed exponential signals in multiplicative and additive noise - Bian, Jiawen; Peng, Huiming; Xing, Jing; Liu, Zhihui; Li, Hongwei (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers parameter estimation of superimposed exponential signals in multiplicative and additive noise which are all independent and identically distributed. A modified Newton?Raphson algorithm is used to estimate the frequencies of the considered model, which is further used to estimate other linear parameters.
Keywords: superimposed exponential signals; modified Newton?Raphson algorithm; multiplicative and additive noise; least squares estimators